DESIGN AND DEVELOPMENT MOBILE APPLICATION OF BUDDHISM E-PARITTA USING FLUTTER FRAMEWORK AND SDLC METHOD - Diny Anggriani Adnas; Charlie Aprilianto (Universitas Internasional Batam, 2022)
Covid-19 pandemic has brought an impact to all kind of activities, including religious worpship activities in Indonesia. Buddhism are the religion was found in india, in general Buddhism are devided to 3 main teachings which is Buddha, Dhamma, and Sangha. Chanting using Parita are practice recommended by Buddha, but due Covid-19 Pandemic many buddhists cannot go to monastery and Paritta is book that provided by monastery. One of the main issues that occur among buddhists during the pandemic was do not have an access to Paritta and did not memorize the chanting script because the language used in Paritta are Pali. However, the solution of that problem is rather simple, one of which is digitalization. This Paritta can be turned into mobile application to help buddhists to access the Paritta. In this study, we have designed a mobile application for Paritta to become E-Paritta using Flutter framework and SDLC Method. Author want to produced a mobile application that have intuitive design, simple workflow and seamless user experience. By designing and developing this mobile application, author are attempt to help people had no access to Paritta